R&D Tax Relief from the Perspective of Green Investment in Poland - Dada, Anna (Publishing House of Wroclaw University of Economics and Business, 2025)
Tax relief for research and development (R&D) activities has been in place in Poland since 2016. This solution is available to a wide range of companies across various industries, and its application is not limited to the domain of environmental projects. Nevertheless, the funds saved on tax liabilities can provide significant support to entrepreneurs in developing products and services in such a way as to reduce their negative impact on the environment. The objective of this chapter is to analyse the current legal provisions concerning R&D tax relief and to attempt to assess the effectiveness of R&D tax relief in the context of supporting green investments in Poland. The interdisciplinary nature of this topic renders it appealing to a broad spectrum of readers, particularly from the standpoint of greening and the application of tools for achieving sustainable development. It appears that there is potential in Poland for the utilisation of R&D tax relief in the context of green investments, however further legislative and educational measures may be required.
Quote as: Dada, A. (2025). R&D Tax Relief from the Perspective of Green Investment in Poland. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), Sustainable Development in Light of Research by Scientists from Poland, Czechia and Slovakia. Different Research Perspectives (pp. 104-118). Publishing House of Wroclaw University of Economics and Business.
Keywords: research and development; tax relief; green investment; sustainable development; income tax